2018
DOI: 10.1037/arc0000044
|View full text |Cite
|
Sign up to set email alerts
|

The devil wears stata: Thin-ideal media’s minimal contribution to our understanding of body dissatisfaction and eating disorders.

Abstract: It is not uncommon for the general public to hear from scholars and advocates that images of thin women in the media are linked to body dissatisfaction and eating disorders among women viewers. However, does the evidence base support such claims? A review of the literature suggests that public claims about media effects in this realm are often misleading and considerable evidence exists to warrant caution in claiming causal effects. Relationships between thin models in media and women's body satisfaction are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
1
10
0
1
Order By: Relevance
“…As hypothesised, greater breast size dissatisfaction was significantly and positively associated with both weight and appearance dissatisfaction. This is consistent with previous work showing that greater breast size dissatisfaction is significantly associated with higher scores on a range of indices of negative body image (Forbes & Frederick, 2008;Frederick et al, 2008;Junqueira et al, 2019;. The most straightforward interpretation of the present finding is that breast size dissatisfaction is an important facet of global negative body image (Swami, Tran et al, 2015).…”
Section: Body Image and Psychological Well-beingsupporting
confidence: 92%
See 2 more Smart Citations
“…As hypothesised, greater breast size dissatisfaction was significantly and positively associated with both weight and appearance dissatisfaction. This is consistent with previous work showing that greater breast size dissatisfaction is significantly associated with higher scores on a range of indices of negative body image (Forbes & Frederick, 2008;Frederick et al, 2008;Junqueira et al, 2019;. The most straightforward interpretation of the present finding is that breast size dissatisfaction is an important facet of global negative body image (Swami, Tran et al, 2015).…”
Section: Body Image and Psychological Well-beingsupporting
confidence: 92%
“…Thus, we would expect significant associations between breast size dissatisfaction and other indices of negative body image. Indeed, the available evidence supports such associations: greater breast size dissatisfaction has been found to be significantly associated with greater body dissatisfaction (Forbes & Frederick, 2008;Frederick et al, 2008;Swami, Cavelti et al, 2015;, greater actual-ideal weight discrepancy (Junqueira et al, 2019;Swami, Cavelti et al, 2015), lower body appreciation (Junqueira et al, 2019;Swami, Cavelti et al, 2015), greater appearance preoccupation (Koff & Benavage, 1998), and greater drive for thinness (Swami, Cavelti et al, 2015). The strength of associations has generally been weak-to-moderate (e.g., , although it should be noted that at least one study found no significant association with body image disturbance (Tantleff-Dunn & Thompson, 2000).…”
Section: Outcomes Of Breast Size Dissatisfactionmentioning
confidence: 89%
See 1 more Smart Citation
“…On the one hand, modern society is exposed to idealization of youth and the thinness presented in the mass-media (Thompson and Heinberg, 1999; Phelps et al, 2007; Striegel-Moore and Bulik, 2007). Several analyses (Murray et al, 1990; Eyal and Te’eni-Harari, 2013; Barcaccia et al, 2018; Ferguson, 2018; Griffiths et al, 2018) show that the body image represented on television, thinspiration/fitspiration websites, and magazine covers is commonly unrealistically thin for women or muscularity unideal for men, not reflecting the range of body shapes in the general population. On the other hand, biological predisposition and family related phenomena are also of significant importance as family provides grounds for comprehensive intellectual, emotional and social development, including personality and self-esteem (SE).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with a study in which adolescent girls showing social comparison tendencies were using manipulated and enhanced images on social media. (21) Both girls and boys often compared themselves with the peers and people around them who they thought had better figure or physique respectively. However, girls compared themselves more with people around them having better figures.…”
Section: Discussionmentioning
confidence: 99%